Jeremiah Day - "If it's for the people, it needs to be beautiful", she said - Cueff, Alain 1960-; Dewey, Fred; Verwoert, Jan 1972-; Stepken, Angelika 1955-; Robinson, Julia 1969- (Badischer Kunstverein, 2021)
Accompanying a series of solo collaborations in 2020, this publication offers the first comprehensive and global perspective on Jeremiah Day's work as an artist, performer, researcher and teacher. As it details Day's specific works and evolution between visual and performing arts and between political reflection and engagement the result also serves as sourcebook for the legacy of the intersection between dance and the visual arts of the 1960s and 70's and the models of cultural practice emerging from the work of Hannah Arendt
Impressum: This book is published accompanying the exhibitions "If It's For The People, It Needs To Be Beautiful, She Said", Badischer Kunstverein, Karlsruhe, 07.02.20 - 19.04.20 / 12.05.20 - 30.08.20; "'Si c'est pour les gens, ça doit être beau', dit-elle", Centre d'art Le Lait, Albi, 26-27.09.20 / 03.10.20 - 29.10.20; "Se è par la gente, deve essere bello, lei disse", Villa Romana, Florence, 13.10.20 - 25.10.20 / 05.05.21 - 28.05.21
Texts by Alain Cueff, Fred Dewey, Jan Verwoert, Angelika Stepken, Julia Robinson
Keywords: Day, Jeremiah -- 1974-; Ausstellungskatalog -- Badischer Kunstverein -- 07.02.2020-19.04.2020 -- 12.05.2020-30.08.2020 -- Karlsruhe; Ausstellungskatalog -- Centre d'art Le Lait -- 26.09.2020-27.09.2020 -- 03.10.2020-29.10.2020 -- Albi; Ausstellungskatalog -- Villa Romana -- 13.10.2020-25.10.2020 -- 05.05.2021-28.05.2021 -- Florenz